THE INFLUENCE OF LEADERSHIP STYLE AND WORKLOAD ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Marnoto, Marnoto; Dwiyono, Gatot; Ruyani, Nur Ahmad (Institut Pendidikan Tapanuli Selatan, 2025)
This study aims to analyze the impact of leadership style and workload on employee performance, with job satisfaction serving as an intervening variable at Grand Asrilia Hotel, Bandung. The sample for this research was selected using a non-probability sampling technique, involving 117 employees. The data were analyzed using path analysis. The findings indicate that: (1) leadership style has a significant effect on job satisfaction; (2) workload does not significantly affect job satisfaction; (3) leadership style and workload jointly influence job satisfaction; (4) leadership style significantly impacts employee performance; (5) workload does not significantly affect employee performance; (6) job satisfaction has a significant effect on employee performance; and (7) leadership style, workload, and job satisfaction collectively influence employee performance. Sobel test results reveal that job satisfaction mediates the relationship between leadership style and employee performance but does not mediate the relationship between workload and employee performance.